Fano-resonant mechanism of terajet formation using graphene-covered high-index mesoscale spheres; Optics Letters; Vol. 49, iss. 18 - Paddubskaya A. G.; Novitsky A. V. Andrey Vasiljevich; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich (2024, 2024)
Title screen